Approaches Aimed at Methodological Preparation of Students in Improving the Quality of Education - Abdullayeva Gavhar Ro’zimurod qizi (Scientific Trends, 2025)
This article analyzes the role and importance of modern pedagogical approaches in the formation of students' methodological preparation. Methodological preparation is considered an important factor in the application of theoretical knowledge to practice, the development of independent thinking and problem-solving skills of students. The article highlights the effectiveness of competency-based education, interactive methods, information and communication technologies and reflection methods in the educational process. It also analyzes the possibilities of improving the quality of education through the use of modern technologies.
Keywords: Methodological preparation, pedagogical technologies, interactive methods, competency-based education, digital education, reflection, problem-based learning, project-based learning.